Assessing the gasification performance of biomass: A review on biomass gasification process conditions, optimization and economic evaluation - Ahmad, A.A. (Elsevier Ltd, 2016)
Currently, the use of biomass as an energy source has received a tremendous amount of interest from all over the world due to its advantage in providing a continuous feedstock supply. Moreover, when compared to fossil fuels, biomass fuels possess negligible sulfur concentrations, produce less ash, and generate far less emissions into the air. Biomass has a potential to be a very promising alternative source of raw material for syngas production due to its tremendous availability. Syngas can be produced from the gasification of a biomass. However, this process requires a significant amount of energy due to the endothermic behavior of the reaction. The energy consumption during the gasification process is a major constraint on the thermal efficiency and on the design of the gasifier. Therefore, a substantial improvement and the optimization of the available gasification process are very crucial in developing a sustainable utilization of these renewable natural resources. This review article focuses on highlighting the characteristics and performances of the different types of gasifiers under variable process parameters that will affect the yields of the end products as well as the composition of the gas. The various types of models used in the simulations, the optimization of the gasification conditions and the economic evaluation of the gasification process will also be discussed. Â© 2015 Elsevier Ltd. All rights reserved.